Pathological features of temporal arteries in patients with giant cell arteritis presenting with permanent visual loss. Issue 1 (5th February 2008) - Chatelain, D; Duhaut, P; Schmidt, J; Loire, R; Bosshard, S; Guernou, M; Pellet, H; Piette, J C; Sevestre, H; Ducroix, J P
Abstract : Background: Permanent visual loss (PVL) is the most feared complication of giant cell arteritis (GCA), and its risk factors are still unclear. Objectives: The aim of our study was to assess the pathological features predictive of PVL on temporal artery biopsy (TAB) specimens in patients with GCA. Methods: The slides of 391 TAB specimens from patients with GCA were reviewed by two pathologists without clinical information. Results: A total of 29 patients (26 females and 3 males, mean age 78.3 years) presented with unilateral PVL at the onset of the disease, and 362 patients (258 females, 104 males, mean age 74.7 years), did not. The pathological features strongly predictive for PVL were the presence (p = 0.003), number (p = 0.001) and aggregates of giant cells (p = 0.001), presence of plasmocytes (p = 0.002), thickened intima (p = 0.007), neoangiogenesis (p = 0.001) and degree of arterial occlusion (p = 0.006). Presence of neutrophils, eosinophils, parietal necrosis, calcification in the arterial wall and disruption of the internal elastic membrane were similar in both groups. Total obstruction of the arterial lumen by a thrombus, intensity of the inflammatory cells infiltration and inflammation of small vessels, nerves and veins surrounding the temporal artery were not associated with blindness. In multivariate analysis, only giant cells remained significantly associated with PVL. Conclusion: Giant cells are strongly associated with PVL, with a significant gradient between great risk and large number of giant cells. However, PVL was neither associated with the intensity of the inflammatory infiltrate, nor with the presence of arterial thrombosis.